Pemenuhan Kewajiban Perpajakan Apoteker Pemilik Usaha Apotik Pasca Diundangkanya UU Cipta Kerja - Gusminarti, Gusminarti; Khairani, Khairani; Kurniawan, Fajri (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
In 2021 the government issued Minister of Health Regulation Number 14 of 2021 concerning Standards for Business Activities and Products in the Implementation of Risk-Based Business Licensing in the Health Sector (hereinafter abbreviated as Minister of Health Regulation No. 14 of 2021). In this regulation there are several changes, one of which is that the pharmacy must be owned by a pharmacist. If the pharmacy is not owned by a pharmacist, the capital owner may collaborate with the pharmacist by agreement before a notary. With this provision, there have been several changes for a pharmacist, one of which is regarding the fulfillment of tax obligations. Tax obligations for pharmacists who work only as pharmaceutical technical personnel, their tax obligations that must be fulfilled are only based on the KUP Law and Article 21 of the Income Tax Law Number 36 in 2008, which was most recently refined by Law Number 7 of 2021 concerning Harmonization of Tax Regulations. namely tax deductions by third parties, in this case by pharmacies. Meanwhile, with the Pharmacist's status as a Pharmacy owner, the fulfillment of his tax obligations will increase in accordance with Tax regulations, namely Business Entities. The problem is what if, during the course of the pharmacy business, the pharmacist who owns the pharmacy which was established based on the agreement resigns, what happens to fulfilling his tax obligations. In this regard, there are three problems that the researcher raises, first, what is the description of pharmacy ownership by pharmacists in West Sumatra, second, how to fulfill tax obligations for pharmacists as pharmaceutical workers and pharmacy owners in West Sumatra. third, problems encountered in fulfilling tax obligations by pharmacists who own pharmacies. In West Sumatra, the research uses research methods with an empirical juridical approach, descriptive research type, the data required is primary and secondary data as well as data collection techniques, interviews and document studies, data processing is carried out using qualitative analysis methods. The results of research on pharmacy ownership in West Sumatra are currently in various forms of business, namely Limited Liability Companies and Individual Businesses such as CVs and Firms so that ownership of Pharmacies is still owned by investors and currently there are 5 Pharmacies which are processing the extension of their Pharmacy Business Licenses and some have transferred their ownership to Children of financiers because they have completed their pharmacy studies, and there are also those who are currently processing business permits in the form of individual PT. Meanwhile, the tax obligations carried out by pharmacists as pharmacy business owners have not yet been implemented because currently pharmacies that use pharmacists as pharmacy owners with non-legal entity business forms are still in the process of processing their permits and legal entities. Problems encountered in fulfilling the tax obligations of pharmacists as business owners Pharmacies are still not visible, because the current status of Pharmacists still has the status of a Pharmaceutical Personnel, so their tax obligations are only limited to Income Tax Article 21.